Households' self-selection of a dynamic electricity tariff - Torgeir Ericson (Statistics Norway, Research Department, 2006)
Offering electricity consumers time-differentiated tariffs may increase demand responsiveness, thereby reducing peak consumption. However, one concern is that time-differentiated tariffs may also attract consumers who benefit because of their consumption pattern, even without a corresponding demand response. A discrete choice model applied to data from a residential dynamic pricing experiment indicates that higher demand flexibility increases the propensity of a household to select dynamic tariffs, while favourable consumption patterns do not influence the tariff choice. The offering of dynamic time-differentiated tariffs is then likely to increase the demand response among residential consumers.
Keywords: D10; Q41; 330; demand response; dynamic pricing; electricity tariff; self-selection; rate option.